2020
DOI: 10.3390/molecules25071663
|View full text |Cite
|
Sign up to set email alerts
|

Directing 2D-Coordination Networks: Combined Effects of a Conformationally Flexible 3,2′:6′,3″-Terpyridine and Chain Length Variation in 4′-(4-n-Alkyloxyphenyl) Substituents

Abstract: The synthesis and characterization of 4′-(4-n-propoxyphenyl)-3,2′:6′,3″-terpyridine is described. Five 2D-coordination networks have been isolated by crystal growth at room temperature from reactions of Co(NCS)2 with 4′-(4-n-alkyloxyphenyl)-3,2′:6′,3″-terpyridines in which the n-alkyl group is ethyl, n-propyl, n-butyl, n-pentyl and n-hexyl in ligands 2–6, respectively. The single-crystal structures of [{Co(2)2(NCS)2}.0.6CHCl3]n, [{Co(3)2(NCS)2}.4CHCl3.0.25H2O]n, [{Co(4)2(NCS)2}.4CHCl3]n, [Co2(5)4(NCS)4]n and [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…We have prepared and characterized three isomeric 3,2′:6′,3"-tpy ligands, rac-2, 3 and 4, which possess rac-4′-(4-butan-2-yloxyphenyl), 4′-(2-methylpropoxyphenyl) and 4′-(tert-butoxyphenyl) substituents, respectively. Reactions of these ligands with Co ( [6]. In the latter, a cone of four extended butoxy chains is accommodated with a similar cone in the next sheet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have prepared and characterized three isomeric 3,2′:6′,3"-tpy ligands, rac-2, 3 and 4, which possess rac-4′-(4-butan-2-yloxyphenyl), 4′-(2-methylpropoxyphenyl) and 4′-(tert-butoxyphenyl) substituents, respectively. Reactions of these ligands with Co ( [6]. In the latter, a cone of four extended butoxy chains is accommodated with a similar cone in the next sheet.…”
Section: Discussionmentioning
confidence: 99%
“…3-Acetylpyridine and 4-hydroxybenzaldehyde were purchased from Acros Organics (Fisher Scientific AG, 4153 Reinach, Switzerland), rac-4-(butan-2-yloxy)benzaldehyde, 4-(2-methylpropoxy)benzaldehyde and 4-(tert-butoxy)benzaldehyde from Fluorochem (Chemie Brunschwig AG, 4052 Basel, Switzerland), 1-bromo-2-methylpropane from Sigma Aldrich (Chemie Brunschwig AG, 4052 Basel, Switzerland), and were used as received. 4 -(4-Hydroxyphenyl)-3,2 :6 ,3"-terpyridine was prepared as previously described [6].…”
Section: Generalmentioning
confidence: 99%
“…3b). 25,34 The sheets also move further apart; the distance between the mean planes through the Co atoms in a sheet is 9…”
Section: Going From a 1d-coordination Polymer To 2d-networkmentioning
confidence: 99%
“…In contrast, inter-ring C-C bond rotation affects the spatial properties of the nitrogen lone pairs in 3,2 0 :6 0 ,3 00 -tpy (Scheme 3), and it has been observed that the conformations of both free and coordinated 3,2 0 :6 0 ,3 00tpy ligands respond to changes in crystal packing. [23][24][25] The first 4,2 0 :6 0 ,4 00 -tpy containing coordination polymer, 2[ZnCl 2 (4,2 0 :6 0 ,4 00 -tpy)] n , was described over 20 years ago by González Garmendia and coworkers, 26 and remains the sole example of a structurally characterized extended assembly containing the unfunctionalized 4,2 0 :6 0 ,4 00 -tpy ligand. Use of the Wang and Hanan, 7 and the Kröhnke 8 strategies provides access to a large suite of 4 0 -functionalized 4,2 0 :6 0 ,4 00 -tpy and 3,2 0 :6 0 ,3 00 -tpy ligands, and in the last decade, the number of 1D-, 2D-and 3D-coordination assemblies incorporating such ligands has increased significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the near-planar conformers, conformation III (which can be described as cis , cis ) in Scheme 1 a is ideally suited to the formation of discrete [2 + 2] metallocycles, although this has only been structurally confirmed in a few cases [ 9 , 10 ]. We have recently been focusing on investigations of the assemblies of coordination polymers and networks incorporating ligands 1 – 6 (shown in Scheme 1 b) and revealed how the planar conformation of the 3,2′:6′,3″-tpy (either I or II , trans , trans or cis , trans , respectively, Scheme 1 a) in both [Cu 2 (OAc) 4 L] n 1 D -coordination polymers and [Co(NCS) 2 L 2 ] n 2 D -coordination networks responds to changes in the length of the n -alkyloxy chain [ 11 , 12 ]. A search of the Cambridge Structural Database (CSD v. 5.4.1 [ 13 ]) using Conquest v. 2020.1 [ 14 ] reveals 95 entries for the 3,2′:6′,3″-tpy motif, both in free ligands, protonated ligands, and metal coordination compounds.…”
Section: Introductionmentioning
confidence: 99%